Influence of nanocomposites in extrusion-based 3D printing: a review - Alli, Yakubu Adekunle; Anuar, Hazleen; Manshor, Mohd Romainor; Bankole, Owolabi Mutolib; Abd Rahman, Nurul Amirah; Olatunde, Simeon Kayowa; Omotola, Elizabeth Oyinkansola; Oladoye, Peter Olusakin; Ejeromedoghene, Onome; Suhr, Jonghwan; Sukindar, Nor Aiman; Mohd Nasir, Nur Aimi (Elsevier, 2023)
3D printing is a process used in a variety of industries. This has the potential to replace traditional method of fabrication in the coming years. However, 3D printed parts with a single type of raw material frequently lack robustness, resulting in failed prints. Therefore, enhancing the properties of the materials is critical for applications in a variety of fields. The synergistic combination of nanoparticles (NPs) and 3D printing technologies particularly extrusion based 3D printing may enable the creation of architecture and devices with unprecedented levels of functional integration. This review reports recent developments in the use of nanocomposites (NCs) with 3D printing technology. The outlooks and several important issues in this area are also discussed with the anticipation that this will provide additional insights to the research community.